Laminate for cosmetic evaluation

JP2026165948APending Publication Date: 2026-10-14TOYOBO CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025058614
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0008】 本発明の積層体は、化粧料を塗布してぬり心地の評価や化粧くずれの評価に供することができる。さらに本発明の積層体は、熱硬化性化合物(A)、無機粒子(B)の種類や投入量を変えること、表面被覆層の厚みを変えることで、表面粗さを制御することができる。これにより年齢層別の皮丘の表面粗さを再現した積層体を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165948000001
    Figure 2026165948000001
  • Figure 2026165948000002
    Figure 2026165948000002
Patent Text Reader

Abstract

This invention provides a laminate that can be used to evaluate the feel of applying cosmetics and the resistance to makeup breakdown. [Solution] A laminate for evaluating cosmetics, comprising a base material and a surface coating layer, wherein the surface coating layer is formed by curing a coating film containing at least a thermosetting compound (A) and inorganic particles (B), and the surface roughness (Ra) of the surface coating layer is 0.5 to 2.5 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminate that can be used for evaluating the application feel of cosmetics and evaluating makeup deterioration.

Background Art

[0002] In terms of functionality, great importance is attached to cosmetics that are less prone to makeup deterioration. The surface of human skin consists of fine grooves called sulci cutis and skin ridges separated by the sulci cutis, and fine grooves also exist on the skin ridges. One of the factors causing makeup deterioration is that the oily component of cosmetics and secreted sebum do not accumulate in these grooves but spread on the skin surface, and the relevant area is touched by a hand or the like. Therefore, to evaluate the application feel and makeup deterioration of cosmetics, human skin or a material that mimics human skin is indispensable. When using human skin, the state of the skin surface (such as the distribution of skin grooves) varies due to the influence of the use site, health condition, outside air temperature, humidity, and other factors, so it is difficult to evaluate the application feel and makeup deterioration with good reproducibility. Therefore, as a method for evaluating the application feel and makeup deterioration with good reproducibility using a material that simulates skin, for example, Patent Document 1 (Utility Model Registration No. 3220087) discloses a simplified skin model in which fine geometric pattern wrinkles resembling human skin are formed on the surface of a base made of a soft synthetic resin material.

Prior Art Documents

Patent Documents

[0003]

Patent Document 1

Summary of Invention

Problems to be Solved by the Invention

[0004] However, Patent Document 1 only has a geometric pattern to reproduce the sulci cutis, and has a problem that the application feel and makeup deterioration cannot be evaluated in the same manner as with human skin.

[0005] This invention was made against the backdrop of the problems of the prior art. In other words, the object of this invention is to provide a laminate that can be used for evaluating the feel of applying cosmetics and for evaluating how easily cosmetics break down. [Means for solving the problem]

[0006] As a result of diligent research, the inventors of this invention discovered that the above problems can be solved by the means described below, and thus arrived at the present invention.

[0007] In other words, the present invention consists of the following configuration. [1] A laminate for evaluating cosmetics, comprising a base material and a surface coating layer, wherein the surface coating layer is formed by curing a coating film containing at least a thermosetting compound (A) and inorganic particles (B), and the surface roughness (Ra) of the surface coating layer is 0.5 to 2.5 μm. [2] The thermosetting compound (A) is at least one compound selected from acrylic resins, oxazoline compounds, melamine compounds, and carbodiimide compounds, and the content of the thermosetting compound (A) in the total solid content of the coating film forming the surface coating layer is 3 to 20% by mass. [1] A laminate for evaluating cosmetics as described above. [3] Inorganic particles (B) are particles with an average particle diameter of 0.1 μm or more and less than 1.0 μm (B1), It contains two or more types of particles, including those with an average particle diameter of 1.0 μm or more and those with an average particle diameter of 10.0 μm or less (B2). A laminate for evaluating cosmetic materials as described in [1] or [2], wherein B1:B2 = 85:15 to 30:70 (mass ratio), and the content of inorganic particles (B) in the total solid content of the coating film forming the surface coating layer is 30 to 80% by mass. [4] A laminate for evaluating cosmetics according to any one of [1] to [3], wherein the base material is a white polyester film containing cavities. [Effects of the Invention]

[0008] The laminate of the present invention can be used to evaluate the feel of application and the resistance to makeup breakdown by applying cosmetics to it. Furthermore, the surface roughness of the laminate of the present invention can be controlled by changing the type and amount of thermosetting compound (A) and inorganic particles (B), and by changing the thickness of the surface coating layer. This makes it possible to provide a laminate that reproduces the surface roughness of skin ridges for different age groups. [Modes for carrying out the invention]

[0009] <Laminate> The laminate in the present invention comprises a substrate and a surface coating layer, wherein the surface coating layer is formed by curing a coating film containing at least a thermosetting compound (A) and inorganic particles (B), and the surface roughness (Ra) of the surface coating layer is 0.5 to 2.5 μm. If the surface roughness (Ra) of the surface coating layer of the laminate of the invention is within the above range, it can be suitably used for evaluating the feel of applying cosmetics and the resistance to makeup breakdown. Furthermore, the laminate according to the present invention may contain other components as needed, as long as they do not impair the effects of the present invention. In this specification, unless otherwise specified, the compounds exemplified as components may be used individually or in combination of two or more.

[0010] <Base material> The base material in this invention includes plastic film, fabric, paper, metal, and boards, but is preferably a plastic film. As the plastic film, various polymer films can be used, such as polyolefin, polyester, polyamide, polyimide, polycarbonate, polystyrene, polymethacrylate, and polyvinyl chloride. Among these, polyester film is preferred from the viewpoint of heat resistance, strength, and stiffness.

[0011] There are no particular restrictions on the thickness of the substrate, but to ensure general strength characteristics, it is preferably 1 to 500 μm, and more preferably 10 to 300 μm.

[0012] The color of the substrate is not particularly limited, but is preferably white. Examples of white substrates include white polyester film. When the substrate is white, it is easier to evaluate the breakdown of cosmetics by visual inspection, as well as by processing color information such as XYZ information, Lab information, spectral information, and color reproduction images. The light transmittance of the substrate is 30% or less, preferably 20% or less, and more preferably 15% or less. A transmittance of 30% or less is preferable because the back side does not show through, which is good for evaluating makeup breakdown.

[0013] From the viewpoint of ease of application of cosmetics, it is preferable that the base material contains fine cavities within the base material. The porosity of the base material, that is, the percentage of the volume of cavities within the base material, is preferably 10 to 50 volume%, more preferably 10 to 30 volume%. If it is less than 10 volume%, the base material will lack cushioning and have a stiff feel, which will affect the evaluation of the application feel. If the cavity content exceeds 50 volume%, the base material will break when evaluating the application feel and makeup breakdown.

[0014] When selecting and using a white polyester film as the base material, it is also acceptable to use a material in which polyester and one or more thermoplastic resins that are incompatible with the polyester are blended together as the film material, and after film formation, at least uniaxial stretching is performed, preferably biaxial stretching in the longitudinal and transverse directions, thereby forming numerous fine cavities inside the film and using a cavity-containing polyester film with an apparent specific gravity of 0.8 to 1.3.

[0015] A corona treatment layer or an easy-adhesion layer may be provided on the surface of the substrate to enhance adhesion to the surface coating layer. As a method for forming the easy-adhesion layer, a coating method is common, and specifically, a gravure coating method, a kiss coating method, a dip method, a spray coating method, a curtain coating method, an air knife coating method, a blade coating method, a reverse roll coating method and the like can be adopted. As for the timing of application, any method may be adopted, such as a method of applying before stretching the film, a method of applying after longitudinal stretching, or a method of applying to the film surface after the orientation treatment is completed, but in order to enhance the adhesion of the coating layer, the most preferable one is an in-line coating method in which a coating liquid is applied by the aforementioned application method to at least one side of a substrate film stretched in a uniaxial direction, and then the film is further stretched in a direction perpendicular to the previous uniaxial stretching direction.

[0016] <表面被覆層> The surface coating layer of the present invention is formed by curing a coating film containing at least a thermosetting compound (A) and inorganic particles (B), and the surface roughness (Ra) of the surface coating layer is 0.5 to 2.5 μm.

[0017] The thickness of the surface coating layer of the present invention is preferably 2 to 30 μm. A thickness of 2 μm or more is preferable because a volume for absorbing oil agents and moisture contained in cosmetics can be secured. A thickness of 30 μm or less is preferable for evaluating the ease of applying cosmetics and makeup deterioration, since the strength of the surface coating layer can be maintained and powder falling can be prevented at 30 μm or less.

[0018] The surface roughness (Ra) of the surface coating layer of the laminate of the present invention is preferably 0.5 to 2.5 μm. Within the above range, it can be suitably used for evaluating the ease of applying cosmetics and makeup deterioration. The surface roughness (Ra) of the present invention means a value measured using a calculation formula conforming to ISO 4287:1997. Ra can be controlled by the type, average particle diameter and content of the inorganic particles used, the solid content concentration of the coating agent, and the thickness of the surface coating layer.

[0019] <熱硬化性化合物(A)> The thermosetting compound (A) is at least one compound selected from the group consisting of acrylic resins, oxazoline compounds, melamine compounds, and carbodiimide compounds, and the content of the thermosetting compound (A) in the total solid content of the coating film forming the surface coating layer is 3 to 20 mass%,

[0020] Examples of the thermosetting compound (A) used in the present invention include thermosetting acrylic resins, urethane resins, oxazoline compounds, melamine compounds, carbodiimide compounds, epoxy resins, ester resins, alkyd resins, and the like. Mixtures of these resins with other resins can also be used. From the viewpoint of increasing the surface hardness, preferred examples of the thermosetting compound include acrylic resins, urethane resins, oxazoline compounds, melamine compounds, and carbodiimide compounds, acrylic resins, oxazoline compounds, melamine compounds and carbodiimide compounds are preferably used, oxazoline compounds, melamine compounds and carbodiimide compounds are particularly preferably used, and melamine compounds are most preferably used.

[0021] Examples of the thermosetting acrylic resin include, but are not limited to, those having a hydroxyl group, methylol group, ethylol group, butyrol group, alkoxymethyl group, alkoxyethyl group, alkoxybutyl group, epoxy group, imino group or the like in the main chain and / or side chain.

[0022] Examples of thermosetting urethane resins include various polyurethane resins, polyurethane polyurea resins, and their prepolymers. Specific examples of such urethane resins include reaction products of diisocyanate components such as tolylene diisocyanate, xylene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, and dicyclohexyl diisocyanate with diol components such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, cyclohexanedimethanol, bisphenol, polyester diol, polyetherdiol, polycarbonate diol, and polyethylene glycol; and reaction products of urethane prepolymers having isocyanate groups at the ends with amino compounds, aminosulfonates, polyhydroxycarboxylic acids, and bisulfites. Furthermore, catalysts can be used to increase reactivity.

[0023] Thermosetting oxazoline compounds are compounds having an oxazoline group in their molecule, and polymers containing an oxazoline group are particularly preferred. These can be produced by polymerization of an addition-polymerizable oxazoline group-containing monomer alone or with other monomers. Examples of addition-polymerizable oxazoline group-containing monomers include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline. One or more of these can be used. Among these, 2-isopropenyl-2-oxazoline is industrially readily available and therefore preferred. Other monomers are not limited as long as they are copolymerizable with addition-polymerizable oxazoline group-containing monomers, for example (meth)acrylic acid esters such as alkyl (meth)acrylates (alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, 2-ethylhexyl, and cyclohexyl groups); unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, styrene sulfonic acid and their salts (sodium salt, potassium salt, ammonium salt, tertiary amine salt, etc.); unsaturated nitriles such as acrylonitrile and methacrylonitrile; (meth)acrylamide, N-alkyl(meth)acrylamide, N,N- Examples of unsaturated amides such as dialkyl(meth)acrylamide (alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, 2-ethylhexyl, and cyclohexyl groups); vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether and ethyl vinyl ether; α-olefins such as ethylene and propylene; halogen-containing α,β-unsaturated monomers such as vinyl chloride and vinylidene chloride; and α,β-unsaturated aromatic monomers such as styrene and α-methylstyrene. One or more of these monomers can be used, and a catalyst can be used to increase reactivity.

[0024] Thermosetting carbodiimide compounds can be synthesized using conventionally known techniques, and generally, a condensation reaction of diisocyanate compounds is employed. The diisocyanate compound is not particularly limited and can be either aromatic or aliphatic. Specifically, examples include tolylene diisocyanate, xylene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexyl diisocyanate, and dicyclohexylmethane diisocyanate. It is also possible to use a catalyst to increase reactivity.

[0025] Thermosetting melamine compounds are compounds that have a melamine skeleton in their composition. For example, alkylolated melamine derivatives, compounds partially or completely etherified by reacting alkylolated melamine derivatives with alcohol, and mixtures thereof can be used. Suitable alcohols for etherification include methyl alcohol, ethyl alcohol, isopropyl alcohol, n-butanol, and isobutanol. The melamine compound may be a monomer, a polymer of two or more, or a mixture thereof. Furthermore, compounds in which urea or the like is co-condensed with a portion of the melamine can also be used, and catalysts can be used to increase the reactivity of the melamine compound.

[0026] The content of thermosetting compound (A) in the coating film constituting the surface coating layer is preferably 3 to 20% by mass of the total solid content of the coating film. If it is 3% by mass or less, particle shedding will affect the evaluation of the feel of applying the cosmetic and the resistance to makeup breakdown, resulting in a discrepancy with human evaluation results. If it is 20% by mass or more, the adhesion between the base film and the particle layer will be maintained too much, preventing the cosmetic from wetting and spreading across the laminate, affecting the evaluation of the feel of applying the cosmetic and the resistance to makeup breakdown, resulting in a discrepancy with human evaluation results.

[0027] In addition to the thermosetting compound (A), other functional resins (C) may be used in the coating film that forms the surface coating layer. Examples of functional resins (C) include ester resins, urethane resins, styrene resins, and acrylic resins. Furthermore, mixtures with resins that have high affinity for inorganic particles, such as polyvinyl alcohol, are suitable from the viewpoint of adhesion to the easy-adhesion layer and prevention of detachment of inorganic particles. The mass ratio of thermosetting compound (A) to functional resin (C) is usually (A) / (C) = 10 / 90 to 50 / 50, preferably 20 / 80 to 40 / 60. It is preferable that the content of thermosetting compound (A) is 10% by mass or more of the total mass of thermosetting compound (A) and functional resin (C), as this increases the surface hardness of the surface coating layer and makes it less likely for inorganic particles to detach. On the other hand, if the content of thermosetting compound (A) is 50% by mass or less of the total mass of thermosetting compound (A) and functional resin (C), there is no risk of the coating layer becoming brittle, and its strength is maintained, making it suitable for evaluating the feel of applying cosmetics and makeup breakdown.

[0028] The thermosetting compound (A) and the functional resin (C) can be used in any state—water-soluble, water-insoluble, or as an aqueous dispersion—as long as their effects are not lost. However, considering the dispersibility of inorganic particles, which will be discussed later, it is preferable to use the entire coating agent in an aqueous or water-soluble dispersion state. When used in an aqueous system, in addition to water, alcohols such as methanol, ethanol, and isopropyl alcohol, as well as organic solvents that do not inhibit the reactivity and solubility of the resin, can be used as solvents.

[0029] The functional resin (C) can be directly added to the coating solution, or it can be mixed into the masterbatch of inorganic particles (B) and then included in the coating solution.

[0030] In addition to the aforementioned thermosetting compound (A), inorganic particles (B), and functional resin (C), various additives such as antistatic agents, leveling agents, inorganic particle dispersants, and antioxidants may be added to the surface coating layer.

[0031] <Inorganic particles (B)> Examples of the inorganic particles (B) of the present invention include, but are not limited to, silica, kaolinite, talc, calcium carbonate, zeolite, alumina, barium sulfate, carbon black, zinc oxide, and titanium oxide. Among these, silica and calcium carbonate are particularly preferred.

[0032] The inorganic particles (B) preferably consist of two or more types of particles: particles (B1) with an average particle diameter of 0.1 to 1.0 μm and particles (B2) with an average particle diameter of 1.0 to 10.0 μm. By combining particles with average particle diameters within the above range, it is possible to adjust the surface roughness to a desired range. The preferred mass ratio of B1 to B2 is B1:B2 = 85:15 to 30:70. If B1 is 85 or higher, the surface roughness becomes small, and the evaluation of application feel and makeup breakdown deviates from the evaluation results by humans. If B2 is 70 or higher, particle shedding affects the evaluation of the application feel and makeup breakdown of the cosmetic, and the results deviate from the evaluation results by humans. There are no particular restrictions on the shape of the particles used; spherical, lumpy, rod-shaped, flattened, etc., may be used. There are also no particular restrictions on their hardness, specific gravity, color, etc.

[0033] The inorganic particles (B) may be surface-treated with organic compounds or silicon compounds that have an organic portion within their molecules. In particular, when using a non-water-soluble medium, it is preferable to use inorganic particles (B) that have been surface-treated with organic material.

[0034] Inorganic particles (B) can also be used in combination with organic particles. Examples of organic particles include benzoguanamine particles, cross-linked polystyrene particles, and cross-linked acrylic particles.

[0035] The content of inorganic particles (B) in the total solid content of the surface coating layer is preferably 30 to 80% by mass. If it is less than 30% by mass, the surface roughness will be small, and the evaluation results of application feel and makeup breakdown will deviate from the evaluation results by humans. If it is 80% by mass or more, particle shedding will affect the evaluation results of the cosmetic application feel and makeup breakdown, and will deviate from the evaluation results by humans.

[0036] Inorganic particles (B) may be directly added to a coating agent prepared with a thermosetting compound (A), a functional resin (C), and an aqueous medium. However, to eliminate coarse inorganic particles and obtain the desired dispersed particle size, it is preferable to go through a dispersion process after adding the inorganic particles. Furthermore, it is even more preferable to prepare a masterbatch of inorganic particles in order to obtain the desired dispersed particle size in a short time. Examples of devices for dispersing inorganic particles include ball mills, sand mills, attritors, roll mills, agitators, colloid mills, ultrasonic homogenizers, homomixers, dissolvers, pearl mills, wet jet mills, paint shakers, butterfly mixers, planetary mixers, and Henschel mixers. The average particle size of the dispersed particles is preferably 0.05 to 0.5 μm for the 50% volume mean diameter (Dv50). If Dv50 is less than 0.05 μm, Ra becomes too small, and if Dv50 is greater than 0.5 μm, Ra becomes too large, which deviates from the evaluation results of people regarding application feel and makeup breakdown.

[0037] The method for preparing the coating film is not particularly limited, as the coating agent containing the prepared thermosetting compound (A), inorganic particles (B), and functional resin (C) can be applied to the substrate by the coating method described above.

[0038] The drying and curing temperature after application is preferably between 100°C and 200°C. Above 100°C is preferable because it prevents insufficient drying and curing, and also prevents blocking due to insufficient curing of the thermosetting compound (A). Below 200°C is preferable because, when a film is used as the substrate, it is less likely to shrink or deform due to heat, and it can dry while maintaining its flatness. The drying and curing time after application is preferably 1 second or more and less than 180 seconds. A drying time of 1 second or more is preferable because it prevents insufficient drying and prevents blocking due to insufficient curing of the thermosetting compound (A). A drying time of less than 180 seconds is preferable because it reduces costs from a productivity standpoint.

[0039] <wax> The surface coating layer of the present invention preferably contains 0 to 1.0% by mass of wax components. By containing only 1.0% by mass or less of wax components, the affinity between the binder resin in the toner and the surface coating layer is increased, improving toner fixation. Examples of waxes include various ester waxes, low molecular weight polyolefins such as polyethylene, polypropylene, and polybutene, silicones that exhibit a softening point upon heating, fatty acid amides such as oleamide, erucamide, ricinoleamide, and stearamide, plant-based waxes such as carnauba wax, rice wax, candelilla wax, wood wax, and jojoba oil, animal-based waxes such as beeswax, mineral and petroleum-based waxes such as montan wax, ozokerite, ceresin, paraffin wax, microcrystalline wax, and Fischer-Tropsch wax, and modified versions thereof. Of course, it is also preferable that the surface coating layer does not contain any wax components.

[0040] <Cosmetics> Examples of cosmetics include basic cosmetics, hair cosmetics, makeup cosmetics, body cosmetics, sunscreens, cleansers, and hair dyes. Preferred cosmetics to be evaluated with the laminate of the present invention are basic cosmetics, makeup cosmetics, lotions, and liquid foundations, with lotions and liquid foundations being more preferred. [Examples]

[0041] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples. This is not the case. First, the evaluation method and measurement method used in this invention will be explained.

[0042] (Dispersed particle size) The dispersed particle size was measured as the 50% volume average diameter (Dv50) using a laser diffraction particle size distribution analyzer, SALD-7500nano (manufactured by Shimadzu Corporation). The masterbatch was diluted with deionized water to an absorbance of approximately 0.2, and measurements were performed using a high-concentration measurement unit. The refractive index of the most abundant inorganic particle by mass used was retrieved from the instrument's built-in database, and the dispersed particle size (μm) was calculated.

[0043] (Surface roughness) Surface roughness Ra was measured using the calculation formula in accordance with ISO 4287:1997, and the arithmetic mean roughness was determined. For the measurement, a laser microscope VK-9700 (manufactured by Keyence Corporation) was used, and the arithmetic mean roughness was measured at one point within a 200 μm x 200 μm square area. Four points were randomly measured, and the average value was taken as the surface roughness (unit: μm).

[0044] (Thickness of the surface coating layer) The thickness of the substrate was measured at 10 locations using a contact-type film thickness gauge manufactured by Ono Sokki Co., Ltd., and the arithmetic mean was used as the film thickness. The thickness of the surface coating layer was measured at 10 locations on the laminate using a contact-type film thickness gauge, the arithmetic mean was calculated, and the difference between this and the previously measured thickness of the substrate was used.

[0045] (Evaluation of application feel) Under a 23℃, 50% RH environment, 5 μL of liquid foundation (manufactured by Kirei&CO., ochre) was applied to the fingertips of 10 female subjects in their 20s and 30s with no skin problems. They were then asked to spread the foundation on their cheeks and on the laminate of the present invention in the same way, and a sensory evaluation of the application feel was conducted. The evaluation items were "ease of spreading" during application, "stickiness" after 1 minute of application, and "moisture" after 1 minute of application. The evaluation scale was as follows, and the average value of the 10 subjects was calculated. If the average value was between 0.1 and 2.0 points, the application feel was evaluated in the same way as when evaluated on human skin. For the application feel evaluation, if the average values ​​for "ease of spreading" during application, "stickiness" after 1 minute of application, and "moisture" after 1 minute of application were all between 0.1 and 2.0 points, it was marked as "○", and otherwise as "×". Same: 2 points Slightly the same: 1 point Neither agree nor disagree: 0 points Slightly different: -1 point Different: -2 points

[0046] (Evaluation of makeup longevity) Under 23°C and 50% RH conditions, 5 μL of liquid foundation (Kirei&CO., ochre) was applied to the inner forearm of 10 female subjects in their 20s and 30s with no skin problems. The foundation was then spread onto the laminate of the present invention and a 3 cm diameter circle drawn on the inner forearm. After 5 minutes, the inner forearm and the laminate of the present invention were rubbed with a fingertip that had not been used for application, and the extent of the foundation bleeding outside the circle was visually evaluated. The evaluation scale was as follows, and the average value for the 10 subjects was calculated. If the average value was between 0.1 and 2.0 points, the makeup breakdown could be evaluated in the same way as when evaluated on human skin. Makeup breakdown was evaluated as "○" if the average value was between 0.1 and 2.0 points, and as "×" otherwise. Same: 2 points Slightly the same: 1 point Neither agree nor disagree: 0 points Slightly different: -1 point Different: -2 points

[0047] <Raw materials used> (base material) • CRISPR (registered trademark) K2323: A white polyester film containing cavities, manufactured by Toyobo Co., Ltd. • CRISPR (registered trademark) K1211: Manufactured by Toyobo Co., Ltd. (Cavity-containing white polyester film) • CRISPR (registered trademark) K2312: A white polyester film containing cavities, manufactured by Toyobo Co., Ltd.

[0048] (Thermosetting resin (A)) • Melamine resin (Amidia® M-3, manufactured by DIC Corporation, solid content 80% by mass) • Urethane resin (Elastron® H-3, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., solid content 20% by mass) • Oxazoline group-containing resin (Epocross® WS-300, manufactured by Nippon Shokubai Co., Ltd., solid content 10% by mass)

[0049] (Functional resin (C)) • Polyester resin (Vyronal® MD1200, manufactured by Toyobo Co., Ltd., solids content 34% by mass) • Styrene acrylic resin (Saibinol® EK119, manufactured by Saiden Chemical Co., Ltd., solids content 36% by mass) • Styrene-acrylic resin (KE-1062, manufactured by Seikoh PMC, solids content 43% by mass) • Polyvinyl alcohol (Gosenol® NL-05, manufactured by Nippon Synthetic Chemical Co., Ltd.)

[0050] (Dispersant) • Aron® T50 (manufactured by Toagosei Co., Ltd., solid content 40% by mass)

[0051] (catalyst) • Urethane curing catalyst (CAT-64, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., solid content 14% by mass) Melamine, carbodiimide, oxazoline curing catalyst (Catalyst ACX, manufactured by DIC Corporation, solids content 35% by mass)

[0052] (Inorganic particles B1) • Calcium carbonate (Hakuenka (registered trademark) Pz, manufactured by Shiraishi Calcium Co., Ltd., solid content 100% by mass, average particle size 0.2 μm) • Calcium carbonate (Brilliant®-15, manufactured by Shiraishi Calcium Co., Ltd., average particle size 0.15 μm, solid content 100% by mass) (Inorganic particles B2) • Silica (Silysia 440, manufactured by Fuji Silysia Chemical Co., Ltd., average particle size 6.2 μm, solid content 100% by mass) • Silica (Silysia® 446, manufactured by Fuji Silysia Co., Ltd., average particle size 6.2 μm, solid content 100% by mass) • Calcium carbonate (Callite® KT, manufactured by Shiraishi Calcium Co., Ltd., average particle size 2.3 μm, solid content 100% by mass) • Calcium carbonate (Callite® SA, manufactured by Shiraishi Calcium Co., Ltd., average particle size 3.3 μm, solid content 100% by mass)

[0053] (organic particles) • Cross-linked polystyrene particles (Finepearl PB3011W, manufactured by Sumitomo Chemical Co., Ltd., average particle size 11 μm, solid content 100% by mass)

[0054] (Manufacturing Examples 1-7) <Preparation of inorganic particle masterbatch> 227.0 parts by mass of water, 0.18 parts by mass of "Aron T50" as a dispersant, two types of inorganic particles B1 consisting of calcium carbonate ("Hakutsuka Pz"), 27.8 parts by mass of "Hakutsuka Pz", 55.6 parts by mass of "Brilliant-15"), 31.9 parts by mass of a polyester aqueous dispersion ("Byronaru MD1200", solid content concentration 34% by mass), 87.9 parts by mass of a polyvinyl alcohol aqueous solution ("Gosenol NL-05", solid content concentration 15% by mass), two types of inorganic particles B2 consisting of "Sylysia 440", 40.0 parts by mass of "Callite KT"), and 27.6 parts by mass of "Callite KT" were mixed and dispersed using a colloid mill (model: MK2000, manufactured by Shinmaru Enterprises, Inc.) and a dissolver (model: CA30, manufactured by Eiko Seiki Co., Ltd.) to obtain MB1. The Dv50 of the obtained MB1 was 0.15 μm. The aqueous polyvinyl alcohol solution used was prepared by pre-dissolving "Gosenol NL-05" in deionized water to a solid content concentration of 15% by mass. Here, the polyester aqueous dispersion (product name Byronal®) and polyvinyl alcohol (product name Gosenol®) function as part of the functional resin (C) in the coating film in the subsequent process. Production Examples 2 to 7 were prepared in the same manner as Production Example 1, by blending each material in the respective amounts according to Table 1 to obtain MB2 to 7. The dispersion particle sizes of MB2 to 7 are listed in Table 1.

[0055] (Examples 1-7, Comparative Examples 1-6) <Preparation of coating solution> At room temperature, 340.6 parts by mass of water were added to a beaker equipped with a stirrer. Then, while stirring, 498 parts by mass of MB1, 128.2 parts by mass of Byronal® MD1200 as a binder resin (functional resin (C)), 27.8 parts by mass of Amidia® M-3 as a thermosetting compound (A), and 5.4 parts by mass of Catalyst ACX as a catalyst were sequentially added to prepare the coating solution of Example 1. Examples 2 to 7 and Comparative Examples 1 to 6 were prepared in the same manner as Example 1, by blending each material in the respective amounts according to Table 2. However, in Examples 3 and 4, and Comparative Examples 1, 4, 5, and 6, which used Elastron® H-3, Elastron® H-3 was added first after water was added, followed by the masterbatch, binder resin, other thermosetting compounds, catalyst, and antistatic agent.

[0056] <Coating and drying of the base film> Using a polyester synthetic paper "Crisper K2323" with a thickness of 188 μm as the base material, the coating solution from Example 1 was applied so that the thickness of the surface coating layer after drying was 8 μm, and it was dried at 160°C for 60 seconds to obtain the laminate of Example 1. For Examples 2 to 7 and Comparative Examples 1 to 6, coating, drying, and curing were carried out in the same manner as in Example 1, except that the base material, coating solution, coated surface, and thickness after drying were changed as shown in Table 2, to obtain laminates. The evaluation results of the feel of application and makeup breakdown of each obtained laminate are shown in Table 2.

[0057] [Table 1]

[0058] [Table 2]

[0059] The laminates of Examples 1 to 7 satisfy the surface roughness Ra range of 0.5 to 2.5 μm, and their application feel and makeup breakdown can be evaluated in the same way as when evaluated on human skin. On the other hand, the laminates of Comparative Examples 1 to 6 did not have a surface roughness Ra in the range of 0.5 to 2.5 μm, and therefore, the feel of application and makeup breakdown could not be evaluated in the same way as when evaluated on human skin. [Industrial applicability]

[0060] The laminate of the present invention allows for the evaluation of cosmetics in the same way as human skin, and can therefore be used for evaluating the feel of applying cosmetics and the resistance to makeup breakdown.

Claims

1. A laminate comprising a base material and a surface coating layer, The surface coating layer is formed by curing a coating film containing at least a thermosetting compound (A) and inorganic particles (B). The surface roughness (Ra) of the surface coating layer is 0.5 to 2.5 μm. Laminate for cosmetic evaluation.

2. The thermosetting compound (A) is at least one compound selected from acrylic resins, oxazoline compounds, melamine compounds, and carbodiimide compounds. The laminate for evaluating cosmetics according to claim 1, wherein the content of thermosetting compound (A) in the total solid content of the coating film forming the surface coating layer is 3 to 20% by mass.

3. Inorganic particles (B) Particles with an average particle diameter of 0.1 μm or more and less than 1.0 μm (B1), It contains two or more types of particles, including those with an average particle diameter of 1.0 μm or more and 10.0 μm or less (B2). B1:B2 = 85:15 to 30:70 (mass ratio), A laminate for evaluating cosmetic materials according to claim 1 or 2, wherein the content of inorganic particles (B) in the total solid content of the coating film forming the surface coating layer is 30 to 80% by mass.

4. The laminate for evaluating cosmetics according to claim 1 or 2, wherein the base material is a white polyester film containing cavities.

Citation Information

Patent Citations

  • Simple skin model

    JP3220087U